2008
DOI: 10.1038/sc.2008.54
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure in ball games for wheelchair users

Abstract: Purpose: Wheelchair sports have become popular in Germany. This is important because of the difficulty experienced by wheelchair-dependent people in maintaining cardiovascular health and fitness by daily activities. Increasing energy expenditure (EE; kcal h À1 ) is one of the most effective ways of decreasing risk of cardiovascular disease. The purpose of this study was to evaluate the EE of individuals with spinal cord injury in ball games for wheelchair-dependent persons. Methods: Fourteen tennis players (WT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 17 publications
(19 reference statements)
3
61
0
3
Order By: Relevance
“…These values are similar to those obtained in training sessions 23 (~12) and slightly lower at the end of each set 9 (12.8 ± 1.8 in the first and 13.2 ± 2.5 in the second set). Although the perceptual response to this activity profile is characterised by moderate RPE, there are values greater than 15 ( Table 2), suggesting that there are periods of greater intensity throughout the match.…”
Section: Physiological and Perceptual Demandssupporting
confidence: 74%
See 2 more Smart Citations
“…These values are similar to those obtained in training sessions 23 (~12) and slightly lower at the end of each set 9 (12.8 ± 1.8 in the first and 13.2 ± 2.5 in the second set). Although the perceptual response to this activity profile is characterised by moderate RPE, there are values greater than 15 ( Table 2), suggesting that there are periods of greater intensity throughout the match.…”
Section: Physiological and Perceptual Demandssupporting
confidence: 74%
“…19 The LA obtained in the present study was 1.41 ± 0.43 mmol l −1 . The LA values in WT previously were just from the training sessions 23 and were slightly higher than 2 mmol l −1 . The LA in the present study was lower than that found in wheelchair basketball and wheelchair rugby in training session 23 or wheelchair basketball in game situation.…”
Section: Physiological and Perceptual Demandsmentioning
confidence: 99%
See 1 more Smart Citation
“…is the standard error and n is the sample size. Several studies reported findings by subgroup only, such as male and female or paraplegic and tetraplegic, 3,[24][25][26][27] and it failed to report a mean for the cohort. To enable ease of comparison between studies, subgroup means were combined and a weighted group mean and standard deviation was calculated for each study using the following equation:…”
Section: Discussionmentioning
confidence: 99%
“…Além de caracterizar a modalidade, esses trabalhos são importantes por proporcionar informações acerca da função de cada jogador em quadra, auxiliando na personalização do treinamento de acordo com o volume de jogo de cada jogador, o que possibilita melhora no resultado esportivo. Outros estudos tiveram como foco a análise das sessões de treinamento do RCR como, por exemplo, análise do gasto energético e a intensidade de cada ação técnica [22][23] .…”
unclassified